2021
DOI: 10.15583/jpchrom.2021.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Photodegradation of Crushed- and Suspended Pranoprofen Tablets

Abstract: Herein, we evaluate the photostability of pranoprofen (PP) tablets (NIFLAN ® 75 mg), its powdered and suspended forms. PP is a member of the 2-arylpropionic acid family of NSAIDs. The content of the active compound was monitored by high-performance liquid chromatography (HPLC) using an ODS column with ultraviolet light (UV) detector. The residual amount of PP in the powder was 86.5%, which was comparable to that of in the suspension (85.4%) after UV irradiation for 24 hr. Further UV irradiation (total irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…Colors of samples of generic amlodipine OD tablets after UV irradiation had not changed as in AML OD tablets and NOR OD tablets. This indicates that the photodegradability of amlodipine was enhanced by changing the dosage form from tablets to powders and suspensions, as shown in our previous reports [12,13]. Light emission efficiency of suspension samples is more significant compared to powder samples.…”
Section: Photostabilities Of Amlodipine Od Tablets Their Powdered And...supporting
confidence: 72%
See 1 more Smart Citation
“…Colors of samples of generic amlodipine OD tablets after UV irradiation had not changed as in AML OD tablets and NOR OD tablets. This indicates that the photodegradability of amlodipine was enhanced by changing the dosage form from tablets to powders and suspensions, as shown in our previous reports [12,13]. Light emission efficiency of suspension samples is more significant compared to powder samples.…”
Section: Photostabilities Of Amlodipine Od Tablets Their Powdered And...supporting
confidence: 72%
“…Our previous reports showed that photostabilities of several medicines, including naproxen and pranoprofen tablets, decrease when crushed or suspended tablets are exposed to UV irradiation [12,13]. The different dosage forms and single-dose packaging of several medicines are useful methods to improve the medication compliance of patients, but the beneficial effect of medicines might be weakened when APIs are photodegraded.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the HPLC chromatogram, residual amounts of APIs were not influenced by UV irradiation when tablet samples were irradiated. These results indicated that changing the dosage form of SPL tablets to powders and suspensions decreases the photostability because of the loss of a film coating and the enhancement of a light emission efficiency to their APIs, as shown in our previous reports [ 29 ]. It is possible that the crushing of SPL tablets for the improvement of medication compliance in a clinical situation might result in the decrease in its beneficial effect when SPL powders are packaged and stored in a place where they are exposed to sunlight.…”
Section: Resultssupporting
confidence: 80%
“…Next, the photostability evaluation of several tablets including NSAIDs and dihydropyridine drugs and their powders and suspensions was performed. The effect of UV irradiation on nine NSAIDs tablets was evaluated as shown in Table 1 [47,48]. Residual amounts of APIs did not decrease when the tablets were UV-irradiated.…”
Section: The Photostability Evaluation Of Several Medicines and Their...mentioning
confidence: 99%